G420 An interim analysis of the go-child birth cohort shows a high prevalence of nasal symptoms in 12 month old children. (27th April 2015) - Strange, E; Basu, K; Rabe, H; Seddon, P; Memon, A; Palmer, C; Tavendale, R; Inglis, S; Quin, M; Mukhopadhyay, S
Abstract : Aims: The aim of this report is to use the GO-CHILD birth cohort to map the prevalence of atopic diseases in children in the UK at 1 year. Methods: GO–CHILD is a multicentre prospective birth cohort study. 2135 infants were recruited antenatally and followed up by questionnaires to determine the prevalence of infections and atopic symptoms at 3, 6, 12 and 24 months. The 12 month questionnaire ascertains atopic symptoms within the first year of life. Results: From the 1226 1 year questionnaires that have been received, 1123 had been entered and analysed by 3/12/2014. 351 (31%) children had eczema and of these 169 (48%) had this condition for over 6 months. 176 (16%) had experienced dry cough unrelated to infection and 253 (23%) had experienced wheeze. Of those reporting wheeze, 243 (96%) had developed the wheeze during or soon after a viral infection, 161 (60%) had been prescribed salbutamol, 97 (39%) had attended their GP as an emergency and 47 (19%) had been admitted to hospital. 523 (47%) of the children were reported to snore at night and 252 (22%) had a runny or blocked nose unrelated to infection: both symptoms are potentially indicators of allergic rhinitis. 187 (17%) reported a reaction to a food item, of which the most common was cow's milk. Conclusion: These interim results show a high prevalence of wheeze, eczema and nasal symptoms in 1 year old children. These data are in line with previous cohort studies. The Manchester Asthma and Allergy Study (MAAS) showed the prevalence of eczema to be 37% and wheeze to be 28% at 1 year. The ALSPAC study found the prevalence of eczema and wheeze to be 25.6% and 23% respectively between 6 and 18 months of age. However our study shows higher levels of upper respiratory symptoms than MAAS which showed a prevalence of 1–2% by 1 year. This study was funded by SPARKS.